A Clustered Randomized Trial Informing Patients on Dialysis About Their Ability to Donate Organs and Tissues. (September 2020) - Andrews, Ann M.; Zhang, Nanhua; Smith, Allyce Haney; Loughery, Caitlin; Resnicow, Ken; Chapman, Remonia; Jenkins Riley, Holly; Stav, Sheri; Yee, Jerry
Introduction: The transplant waiting list exceeds the number of organs available. One means of increasing the organ pool is to broaden potential donors to include those with chronic diseases. Research Questions: The study tested the effectiveness of using peer mentors to encourage individuals on dialysis to enroll on an organ donor registry. Design: Dialysis units were pair-matched by size and racial composition and then randomized to one of 2 interventions: meetings with a peer mentor (experimental intervention) or organ donation mailings (control). Peer mentors were trained to discuss organ donation with individuals on dialysis during in-person meetings at dialysis units. The primary outcome was verified registration in the state's donor registry. Results: After adjusting for age, gender, race, income, and education and accounting for correlation within the dialysis center, there was a significant intervention effect. Among individuals in the intervention group, the odds of enrolling (verified) on the donor registry were 2.52 times higher than those in the control group. Discussion: The use of peer mentors to discuss donating organs after death with individuals on dialysis can increase enrollment on a donor registry. Dispelling myths about chronic illness and donation can counter widely held misconceptions and help persons make an informed choice about end-of-life decisions and present an opportunity to increase the number of organs and tissues available for transplant.